Особливості структури заморожених кріозахисних розчинів - Sevastianov, Stanislav; Osetsky , Oleksandr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):291